Induced sputum versus gastric aspirate for microbiological confirmation of pulmonary tuberculosis in infants and young children: A prospective cohort study - Beig, Farzana K.; Ali, Mohd Kashif; Naim, Eeman (Indian Journal of Child Health, 2019)
Introduction: The diagnosis of tuberculosis (TB) is challenging in children due to the paucibacillary nature of disease and difficulty in sample collection. Gastric lavage (GL) is recommended in children because children tend to swallow sputum and do not expectorate; however, it is invasive, stressful and requires admission. Objective: The objective of this study was to compare the yield of GL samples with that of induced sputum, which is a non-invasive method and can be done on an outpatient basis. Methods: A prospective cohort study was done on 55 children, who were